Analisis Faktor-Faktor Yang Mempengaruhi Tingkat Pengungkapan Sukarela Laporan Keuangan Pemerintah Daerah - Weni Januar Liza; Fefri Indra Arza (Universitas Negeri Padang, 2019)
This study aims to analyze the factors that influence the voluntary disclosure of local government financial reports. Voluntary disclosure of financial statements is measured using the number of voluntary disclosure items found in financial statements, while the independent variables used in the study are the size of regional government, age of local government, number of regional work units, level of dependency, regional financial independence, regional wealth, opinion audit and profitability ratio. The sample of this study used a total sampling method, in order to obtain a sample size of 57 reports of financial security of local governments in West Sumatra from 2015-2017. The analytical tool used is multiple linear regression. The results of the study show an average voluntary disclosure of financial statements of 7 items. This research shows that the size of the regional government, the age of the regional government, the number of regional work units, the level of dependency, regional financial independence, regional wealth, audit opinion, and profitability ratio are not proven to have an effect on voluntary disclosure of regional financial statements